Ecology and Genetics of Natural Populations of North American Vitis Species Used as Rootstocks in European Grapevine Breeding Programs - Arnold, Claire; Schnitzler, Annik (Frontiers in Plant Science, 2020)
Three North American Vitis species (V. riparia, V. berlandieri, V. rupestris) became widely used in rootstock breeding programs following the expansion of North American pests and diseases introduced in vineyards of the world during the 19th century. When they escape, they become feral in the most dynamic parts of Mediterranean floodplains. To better understand this ongoing process, we studied the ecology of Vitis species in their native sympatric range. We analyzed in deep 61 plots of 710m2 containing Vitaceae species along 216km of the Buffalo River and adjacent plateaus (Arkansas, USA). We investigated the populations structure and genetics of the Vitis complex (i.e., possible hybrids and the Vitis species) and the sharing of habitats with other Vitaceae (Muscadinia rotundifolia and Parthenocissus quinquefolia). Vitaceae share space according to their life strategies and microhabitat along ecological gradients. The plateau niche seems optimal for V. berlandieri and V. aestivalis. V. berlandieri is also found in alluvial zones. The most erosive parts of the river are colonized by V.rupestris, whereas the first terraces include most of the M. rotundifolia populations. Vitis riparia and Parthenocissus live in the largest range of forest habitats, from plateaus to alluvial forests, and from the forest floor to the canopy, with the highest densities along the river. Interestingly, natural hybridization can occur, but establishment success is rare and limited to alluvial forests. In their native range these populations are controlled by biotic and abiotic conditions. In Europe the biotic relations among species are different. Our study shows that V. riparia and its hybrids could be the best candidates for a large scale invasion.